Synthetic nanofillers in polymer composites for aerospace industry - Asyraf M.R.M.; Syamsir A.; Nurazzi N.M.; Norrrahim M.N.F.; Hassan S.A.; Ilyas R.A.; Abdul Saad W.A.; Rafidah M.; Sharma S.; Razman M.R.; Rashid M.Z.A. (Elsevier, 2024)
Synthetic nanofillers such as carbon nanotubes and montmorillonite have seen good progress and have been widely applied in polymer composites in recent years. They have been applied in applications such as portable electronic devices, entertainment, sports, and especially within the aerospace sector. They have been applied in aerospace applications because synthetic nanofiller-based composites offer improved mechanical, thermal, and electrical properties. Additionally, they possess a low density and noteworthy stiffness as nanofillers in polymer composites. As mechanical nanoreinforcements for structural applications, they have unique nano dimensions and sizes, as well as incredible strength. This chapter provides an overview of the application of synthetic nanofiller-based polymer composites in aerospace and also highlights the key factors influencing their performance. 2023 Elsevier Ltd. All rights reserved.